Antagonistic Activity of Bacteria Isolated from the Periplaneta americana L. Gut against Some Multidrug-Resistant Human Pathogens - Asmaa Amer; Basma Hamdy; Dalia Mahmoud; Mervat Elanany; Magda Rady; Tahani Alahmadi; Sulaiman Alharbi; Sara AlAshaal (MDPI AG, 2021)
The insect gut is home to a wide range of microorganisms, including several bacterial species. Such bacterial symbionts provide various benefits to their insect hosts. One of such services is providing metabolites that resist infections. Little data are available about gut-inhabiting bacteria for several insect groups. Through the present work, the gut bacteria associated with the American cockroach (Periplaneta americana L.) were isolated, identified, and studied for their potential antimicrobial activity against multidrug-resistant (MDR) human pathogens. The cockroaches were collected from three different environmental sites. Gut bacteria were isolated, and sixteen species of bacteria were identified using Vitek MALDI-TOF MS. The antagonistic activity of the identified bacteria was tested against a panel of multidrug-resistant bacteria and fungi, namely: methicillin-resistant Staphylococcus aureus (MRSA) (clinical isolate), Streptococcus mutans Clarke (RCMB 017(1) ATCC ® 25175™) (Gram-positive bacteria), Enterobacter cloacae (RCMB 001(1) ATCC® 23355™) and Salmonella enterica (ATCC® 25566™) (Gram-negative bacteria). The isolates were also tested against human pathogenic fungi such as Candida albicans (RCMB005003(1) ATCC® 10231™), Aspergillus niger (RCMB002005), Aspergillus fumigatus (RCMB002008), Aspergillus flavus (RCMB002002), and Penicillium italicum (RCMB 001018(1) IMI193019). The results indicated that some bacterial species from the cockroach gut could antagonize the growth activity of all the tested pathogens. Such antimicrobial properties could ultimately lead to the future development of therapeutic drugs. The evaluation and mode of action of antagonistic gut bacteria against the most affected MDR pathogens were demonstrated using transmission electron microscopy (TEM).